Effect of polyvinyl alcohol fibers on mechanical properties of nano-SiO2-reinforced geopolymer composites under a complex environment - Zhang Peng; Wang Cong; Guo Zhenhui; Hong Jian; Wang Fei (Nanotechnology Reviews, 2023)
Buildings in service are severely affected by the complex environment with multiple coupled factors such as high temperatures, humidity, and inorganic salt attack. In this work, the mechanical properties of nano-SiO2-reinforced geopolymer composites (NSGPC) incorporated with varying dosages of polyvinyl alcohol (PVA) fibers were investigated under a complex environment. A simulated environmental chamber was employed to simulate the complex environment with relative humidity, temperature, and NaCl solution concentration of 100%, 45°C, and 5%, respectively. Fly ash/metakaolin geopolymer composites (GPCs) were fabricated by utilizing 1.5% nano-SiO2 by weight and five various dosages of PVA fibers by volume (0, 0.2, 0.4, 0.6, and 0.8%). The compressive strength, tensile strength, elastic modulus, and impact resistance of NSGPC eroded in a simulated environmental chamber for 60 days were determined. Then, the impact of the PVA fiber dosage on the mechanical properties of NSGPC under complex coupled environments was analyzed. In addition, scanning electron microscopy (SEM) was employed to evaluate and analyze the microstructural behavior of NSGPC under complex environments. Results indicated that the compressive strength, tensile strength, elastic modulus, and impact resistance of NSGPC increased with increasing PVA fiber to 0.6% and then decreased with a continuous increase to 0.8% but remained higher than those of the reference specimen. NSGPC exhibited the best performance at a PVA fiber dosage of 0.6%, which increased by 13.3, 12.0, 17.2, and 522%, respectively. The outcomes of SEM analysis indicated that the usage of PVA fiber and NS remarkably improved the mechanical properties and microstructural behavior of GPC by making the inner structure of GPCs more robust and compact under a complex environment. The outcomes of this work can provide theoretical guidance for buildings serving under a complex environment.